The neurology of eye movements - Leigh, R. John; Zee, David S. ([New York] : Oxford University Press, 2015)
The fifth edition of the'Neurology of Eye Movements' provides a modern synthesis of basic aspects of the control of eye movements and their application to clinical disorders affecting the brain, eye or ear.
This edition previously issued in print: 2015.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 15, 2016).
Keywords: Eye -- Movement disorders; Neuroophthalmology